2018
DOI: 10.2340/00015555-2939
|View full text |Cite
|
Sign up to set email alerts
|

Lower-limb Ulcers in Systemic Sclerosis: A Multicentre Retrospective Case-control Study

Abstract: Lower-limb ulcers in systemic sclerosis patients are rarely reported. The aim of this study was to describe the main causes and outcomes of lower-limb ulcers in systemic sclerosis patients and to assess factors associated with ischaemic causes (arterial disease and/or microvascular impairment). A retrospective, multicentre, case-control study was conducted in 2013 and 2014, including 45 systemic sclerosis patients presenting lower-limb ulcers between 2008 and 2013. The estimated prevalence of lower-limb ulcers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…10 Similarly, 24/25 patients in our series had previous ulcer of lower limbs before amputation. Bohelay et al 14 reported six amputations of lower limbs in 43 SSc patients with lower limb ulcers. Thus, patients suffering from SSc and lower limb ulcer(s) appear to be at high risk for amputation and should be followed vigilantly.…”
Section: Discussionmentioning
confidence: 99%
“…10 Similarly, 24/25 patients in our series had previous ulcer of lower limbs before amputation. Bohelay et al 14 reported six amputations of lower limbs in 43 SSc patients with lower limb ulcers. Thus, patients suffering from SSc and lower limb ulcer(s) appear to be at high risk for amputation and should be followed vigilantly.…”
Section: Discussionmentioning
confidence: 99%
“…Shanmugam et al 11 calculated a 4% (N=249) prevalence of ulcers in the lower limbs of systemic sclerosis patients. In a study by Bohelay et al 12 of 45 patients, the estimated prevalence of lower limb ulcers was 12.8%, and the etiologies consisted of 22 cases of venous insufficiency (49%), 21 cases of ischemic causes (47%), and 2 cases of other causes (4%).…”
Section: Calcinosis Cutis Due To Systemic Sclerosis Sine Sclerodermamentioning
confidence: 97%
“… - Anti-TOPO/anti-Scl-70 signifies an increased risk for fibrosis, especially in the lungs, 18 scleroderma renal crisis, and skin ulceration. 19 Conversely, their absence indicates a better prognosis and survival. 20 - ACA in lcSSc patients 21 indicates a higher risk of pulmonary hypertension and gastrointestinal involvement.…”
Section: Significancementioning
confidence: 99%
“…- Anti-TOPO/anti-Scl-70 signifies an increased risk for fibrosis, especially in the lungs, 18 scleroderma renal crisis, and skin ulceration. 19 Conversely, their absence indicates a better prognosis and survival. 20 …”
Section: Significancementioning
confidence: 99%